Hubungan Metode Pembelajaran Al-Quran Dan Minat Anak Usia Dini - Ermaini, Ermaini (Yayasan Darusssalam Bengkulu, 2021)
Learning the Koran should be mandatory at an early age as part of the Muslim community. The Qur'an is described as a guide. The Qur'an is the holy book which is the main source for Muslims. using Al-Qur'an learning methods to make it easier for children to become accustomed to quickly, skillfully, accurately and effectively in reading the Qur'an. The aim of the researcher in conducting this research is 1) to find out the method of learning the Al-Qur'an at TKIT Rabbani, Bengkulu. 2) to find out the factors that support children's interest in reading the Al-Qur'an. 3) to find out the activities carried out by teachers to increase children's interest at TKIT Rabbani, Bengkulu. This research uses descriptive qualitative research, data collection techniques through observation, interviews and documentation. The results of the research are that educators use the talaqqi method which applies the mouth-to-mouth method or the teacher will read verses from the Koran and the students will listen then the children will repeat back what the teacher read. Before carrying out Al-Qur'an reading activities, children will be invited to perform dhuha prayers, dhikr, then continue with memorizing hadiths and writing the basic letters of the Al-Qur'an.